Akibat Hukum Tidak Terlaksananya Kewajiban Pemeliharaan Anak (Alimentasi) Oleh Orang Tua Pasca Putusan Perceraian - Ilham Jafar; Nur Mohamad Kasim; Dolot Alhasni Bakung (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This research aims to find out how child maintenance cases (alimentation) are resolved by parents after divorce in the Gorontalo Religious Court and what the legal consequences are if parents do not carry out their child maintenance obligations (alimentation) after a divorce decision in the Gorontalo Religious Court. This research uses empirical research. This research is research originating from field observations and uses a descriptive qualitative approach. The results of this research show that the case resolution process involves lawsuits, trials and mediation. If mediation fails, the Religious Court issues a decision. However, sometimes the losing party does not comply with the decision. Winners can request execution, including confiscation of property or salaries. In this case, the father is still obliged to support the child after the divorce, but implementation is problematic. Some fathers are reluctant to fulfill this obligation. The Religious Courts play an important role in enforcing this. Research emphasizes the protection of children's rights and law enforcement to fulfill post-divorce livelihoods. Meanwhile, the legal consequences of non-fulfillment of child maintenance (alimentation) by an ex-husband who does not comply with the decision, the party who wins in the trial can submit a request to the Chair of the Religious Court to force the implementation of the decision and carry out the execution. If within a certain time the ex-husband still does not comply with the decision, the winning party can ask for the ex-husband's property to be confiscated, but still pay attention to the father's financial condition.